ANALISIS SEKTOR BASIS DAN SUBSEKTOR PERTANIAN BASIS TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN KEEROM, PROVINSI PAPUA - Usman Usman (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
Agricultural  development  program  in  Indonesia  is  the  part  of  economic development.  Papua  Province  in  the  economic  sector,  the  agriculture  sector  is  the very important role in supporting economic growth in the region.This study aims to analyze  the  basic  sector  and  basic  sub-sector  of  agriculture,  analyze  the  position sector  and  the  agriculture  sector  in  the  future,  and  the  determinants  of  changes  in positions on regional economic growth based on the calculation of the GDP Keerom district  and  Papua  province  in  2008-2011.The  study  used  secondary  data  over  a period of four years. The analysis  method used is Location Quotient (LQ), Dynamic Location  Quotient  (DLQ),  and  Total  Shift  Share  (TSS).  The  analysis  LQ  show  that agriculture  sector  is  the  basic  sector  in  the  economy  Keerom.While  the  agriculture sector  as  the  sub-sector  basis  (leading  sector) is plantation,  animal  husbandry,  and forestry.The combined method of LQ and DLQ, show that agriculture sector is still the sector basis in the future.The results of the analysis TSS is known that the deciding factor  position  change  on  plantations  and  fishing  sub-sector  is  the  location  factor, while the determining factor position change on the livestock sector is the factor of of economic structure.